Knowledge and Attitude Toward COVID-19 and Vaccine Acceptance among Health Sciences and Non-Health Sciences Students from Two Large Public Universities in Thailand - Hanvivattanakul, Sirashat; Jongmekwamsuk, Kanathip; Vanichanan, Jakaphat; Khawcharoenporn, Thana (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: Data on knowledge and attitude toward COVID-19 and vaccine acceptance among the students may inform the strategies for COVID-19 prevention. Objectives: To assess knowledge, attitudes, and factors related to vaccine acceptance among Thai University students. Methods: An online survey study was conducted among the students from 12 Health Sciences faculties (HS) and from 16 non-Health Sciences faculties (NHS) of two universities in Thailand from October 2021 to January 2022. Results: There were 1,728 participating students; 613 (35%) were HS and 1,115 (65%) were NHS. The median knowledge scores about COVID-19 were significantly higher among HS compared with NHS (15 vs. 13). HS were more knowledgeable than NHS about the causes, at-risk populations, and vaccines for COVID-19. Overall, the students strongly agreed that people should have an equal chance to choose and receive COVID-19 vaccinesthey want. HS were more likely to agree that wearing a mask and social distancing can reduce the risk of getting COVID-19. In contrast, NHS were more likely to agree that population’s confidence in their government highly affects decision to get vaccinated and COVID-19 should be considered as an economic problem rather than a public health problem. The rate of COVID-19 vaccine acceptance was overall 99.3% and the rate of vaccine acceptance was comparable between HS and NHS. The main reasons for declining vaccination were no availability of wanted vaccines and concerns about vaccine efficacy and safety. Conclusions: There were some different knowledge gaps and attitude toward COVID-19 between HS and NHS. The reasons for declining vaccination should be considered more for improving COVID-19 vaccination among the students.